Reevaluating Successful Franchisees Characteristics - Mohd, Zalena; Mohd , Zahira Ishan (School of Social Sciences, USM, 2017)
This paper presents the literature reviews of a study that evaluate and identify the criteria of a successful franchisees in Malaysia. The report can be adopted by the franchisors in determining the best candidate for the franchise business. A systematic review was conducted to explore and to gather the findings from the empirical journal articles. Articles from 1997 to 2016 were included and analyzed. This method gave a thorough understanding of the franchisee criteria that contributed to the success factors from various perspectives. The findings indicates that entrepreneurial capacity, professional experience, motivation and financial capacity had given direct impact towards determining the best criteria for the sales performance and franchisee success. In addition, personal franchisee characteristics are important for the franchise business success. Result from this study is expected to contribute and to add on to the body of literature on the above subject matter. The author contend that this paper would significantly provide a practical framework for franchisors in the selection process of franchisees.